Pengelolaan Morning Talk dalam Pembentukan Karakter Islami - Hanifah Mardliyah Kurnia; Nan Rahminawati (UNISBA Press, 2024)
Abstract. This research is motivated by the fact that there are still many students who lack This research is motivated by the fact that there are still many students who lack confidence, there are fights between students, children who are ostracized to bullying, and there are still many students who do not care about Islamic character in themselves. This morning talk program aims to provide additional knowledge to students so that they can add insight into (a) planning the morning talk program (b) implementing the morning talk program (c) educator evaluation of the morning talk program. This research uses a qualitative approach with descriptive methods. Data collection methods used interviews, observations, and documentation studies. Data analysis used data reduction, data presentation, and data verification. The results of this study indicate that the management of the morning talk program in Islamic character building at MI Darul Furqan Lembang has been running quite well. Where this can be seen from (a) planning in morning talk activities begins with determining the objectives to be achieved, then students are taught to memorize daily prayers to be applied in everyday life. (b) Implementation in the morning talk program which is held every morning after the dhuha prayer at 08.05-08.20. The implementation of the morning talk program in Islamic character building is carried out through the preparation of teaching meetings held by the student division ahead of the new school year, both regarding the teaching module, the preparation of a rotating schedule of teachers in implementing the program. (c) The evaluation of the morning talk program is that educators monitor students' participation and their understanding of the material presented by conducting periodic tests. So it can be concluded that the management of the morning talk program at MI Darul Furqan Lembang is effective in shaping students' Islamic character. Abstrak. Penelitian ini dilatarbelakangi oleh masih banyaknya siswa yang kurang percaya diri, adanya pertengkaran antar siswa, anak yang dikucilkan sampai dengan bullying, serta masih banyak siswa yang belum memperdulikan karakter Islami dalam dirinya. Program morning talk ini bertujuan untuk memberikan pengetahuan tambahan kepada siswa guna memperluas wawasan untuk mengetahui (a) perencanaan program morning talk (b) pelaksanaan program morning talk (c) evaluasi pendidik terhadap program morning talk. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Metode pengumpulan data dengan menggunakan wawancara, observasi dan studi dokumentasi. Adapun analisis datanya menggunakan reduksi data, penyajian data, dan verifikasi data. Hasil penelitian ini menunjukkan bahwa pengelolaan program morning talk dalam pembentukan karakter Islami di MI Darul Furqan Lembang sudah berjalan cukup baik. Dimana hal tersebut dapat terlihat dari (a) perencanaan dalam kegiatan morning talk dimulai dengan menentukan tujuan yang ingin dicapai, kemudian peserta didik diajarkan untuk menghafal doa-doa harian untuk diterapkan dalam kehidupan sehari-hari. (b) Pelaksanaan di dalam program morning talk tersebut dimana dilaksanakan setiap pagi hari setelah shalat dhuha pada pukul 08.05-08.20. Pelaksanaan program morning talk dalam pembentukan karakter Islami dilakukan melalui persiapan rapat ajar yang diadakan oleh divisi kesiswaan menjelang tahun ajaran baru, baik itu mengenai modul ajar, penyusunan jadwal bergilir bagi para guru dalam pelaksaan program tersebut. (c) Evaluasi dari program morning talk yaitu pendidik memantau partisipasi peserta didik dan pemahamannya terkait materi yang disampaikan dengan mengadakan tes secara rutin. Maka dapat disimpulkan bahwa pengelolaan program morning talk di MI Darul Furqan Lembang sudah efektif dalam pembentukan karakter Islami siswa-siswi.